2011
DOI: 10.1002/poc.1868
|View full text |Cite
|
Sign up to set email alerts
|

Reduction potentials of para‐substituted nitrobenzenes—an infrared, nuclear magnetic resonance, and density functional theory study

Abstract: Formal reduction potentials, E°′, of a series of 12 para‐substituted nitrobenzenes (R―C6H4―NO2, where R═NH(CH3), NH2, OCH3, CH3, H, OCO(CH3), Cl, CF3, CO(CH3), CO(H), CN, and NO2) were measured and related to experimental parameters and the calculated descriptors: the lowest unoccupied molecular orbital (LUMO) energy (ELUMO), electron affinity (EA), electrophilicity index (ω), and relative group electronegativity (χR). Excellent correlation was obtained in the linear relationship between E°′ and both ELUMO (R2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
56
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(65 citation statements)
references
References 59 publications
9
56
0
Order By: Relevance
“…These data may be used for answering the question: Does the electron acceptance of the nitro group (i.e., electroreduction) in various chemical species follow the trend in EAP values estimated by using of the cSAR concept? Table 1 presents the half-wave potentials (E 1/2 ) for p-nitrobenzene-X derivatives measured in dimethylformamide with tetrammonium perchlorate as a supporting electrolyte [16] as well as the formal reduction potentials (E 0 ) measured in dry acetonitrile with tetra-n-butylammonium hexafluorophosphate as supporting electrolyte [17], substituent X constants (r p , r p ? ) and cSAR values.…”
Section: Csar(no 2 ) As a Numerical Characteristic Of The Eap Of The mentioning
confidence: 99%
See 1 more Smart Citation
“…These data may be used for answering the question: Does the electron acceptance of the nitro group (i.e., electroreduction) in various chemical species follow the trend in EAP values estimated by using of the cSAR concept? Table 1 presents the half-wave potentials (E 1/2 ) for p-nitrobenzene-X derivatives measured in dimethylformamide with tetrammonium perchlorate as a supporting electrolyte [16] as well as the formal reduction potentials (E 0 ) measured in dry acetonitrile with tetra-n-butylammonium hexafluorophosphate as supporting electrolyte [17], substituent X constants (r p , r p ? ) and cSAR values.…”
Section: Csar(no 2 ) As a Numerical Characteristic Of The Eap Of The mentioning
confidence: 99%
“…The variability of its EAP is nicely illustrated by experimental measurements of the polarographic half-wave potentials, E 1/2 , of the reversible one-electron reduction of substituted nitrobenzene derivatives carried out in aprotic solvents to avoid subsequent kinetics [16], as well as by their formal reduction potentials [17], E 0 . In this way, the obtained E 1/2 as well as E 0 values are thermodynamic properties and may serve as reliable descriptors of relations between structure and energetic characteristics of the molecules.…”
Section: Introductionmentioning
confidence: 99%
“…[ 30,35,36 ] For molecules closely related in structure, reduction potentials are linearly related to the LUMO energies. [ 43 ] Using density functional theory calculations, Andrzejak et al [ 44 ] have demonstrated that altering the aromatic system from PMDA to NTCDA and PTCDA lowers the LUMO energy and thus the increased average discharge voltage from PMDA-based to NTCDA-based and PTCDA-based PIs is reasonable. We expect a substitution with much stronger electronwithdrawing groups, such as cyano and bromine, will enable further elevation of the redox potential of PIs.…”
mentioning
confidence: 98%
“…Next, photoredox catalysis of I was investigated. Since the redox potential of the photo‐reduced I by two electrons (−1.25 V vs. NHE in acetonitrile) is more negative than those of oxygen (−0.65 V vs. NHE in acetonitrile)12 and nitrobenzene and its substituted ones (varying from −1.2 to −0.8 V vs. NHE in acetonitrile),13 the reduction of oxygen and various nitroarenes is thermodynamically possible in the present photoredox system. As expected, the photo‐reduced I was readily reoxidized by exposure to air, and the color of the solution changed from dark blue to pale yellow, indicating that electron transfer from the photo‐reduced I to oxygen proceeds.…”
Section: Photocatalytic One‐pot Synthesis Of N‐(4‐methoxybenzylidene)mentioning
confidence: 92%